On Monolayer Formation of Pyrenebutyric Acid on Graphene - Hinnemo, Malkolm (Langmuir : the ACS journal of surfaces and colloids, 2017)
As a two-dimensional material with high charge carrier mobility, graphene may offer ultrahigh sensitivity in biosensing. To realize this, the first step is to functionalize the graphene. This is commonly done by using 1-pyrenebutyric acid (PBA) as a linker for biomolecules. However, the adsorption of PBA on graphene remains poorly understood despite reports of successful biosensors functionalized via this route. Here, the PBA adsorption on graphene is characterized through a combination of Raman spectroscopy, ab initio calculations, and spectroscopic ellipsometry. The PBA molecules are found to form a self-assembled monolayer on graphene, the formation of which is self-limiting and Langmuirian. Intriguingly, in concentrated solutions, the PBA molecules are found to stand up and stack horizontally with their edges contacting the graphene surface. This morphology could facilitate a surface densely populated with carboxylic functional groups. Spectroscopic analyses show that the monolayer saturates at 5.3 PBA molecules per nm2 and measures ∼0.7 nm in thickness. The morphology study of this PBA monolayer sheds light on the π-π stacking of small-molecule systems on graphene and provides an excellent base for optimizing functionalization procedures